Kebijakan Belanja Desa Untuk Pemberdayaan Masyarakat - Dahlan Tampubolon; Mardiana Mardiana (Universitas Musamus, Merauke, Papua, 2022)
Village expenditure is critical for improving public services and welfare, but it is not yet felt by the community to its full potential. Village spending continues to be dominant for village officials' expenditures and physical activities. The objective of this research is to examine the involvement, transparency, and appropriateness of village spending. Additionally, this study examines the relationship between village spending and knowledge, technological ability, and village development. Forty-five participants were interviewed, including 18 village officials and representatives from 27 communities. Contingency table and rank Spearman correlation are the two primary analytic tools. Village expenditures in Kampa District, Kampar Regency, Riau Province, averaged over one billion rupiah, according to research. Village expenditures on community empowerment are distributed according to each village's needs. The majority of communities participate in the planning, implementation, and administration of village expenditures. There is no significant difference in the community's and village officials' perceptions of community involvement and transparency in village spending. Between village officials and the community, there are differences in perceptions of the suitability and accuracy of village spending. Spending in villages fosters community empowerment. There is a strong correlation between village expenditure and the development of community capacity and understanding. The capacity to use technology is also related to the amount of money spent by villages on empowerment. The majority of village officials and members of the community stated that village expenditure on empowerment had resulted in increased village development.